KESEHATAN MENTAL IBU PASCA ABORTUS DI RUANG VK BERSALIN RUMAH SAKIT UMUM DAERAH PANGERAN JAYA SUMITRA KOTABARU - Rahmadhalena, Ade; Sismeri Dona; Putri Vidiasari (Midwifery And Complementary Care, 2023)
Background:Mental health is a condition in which an individual is free from all symptoms of mental disorders. The psychological state of women during pregnancy who experience abortion can be traumatic, often resulting in anxiety, emotional disturbances, and depression. About 50% of women experience psychological disorders within weeks to months following an abortion. Objective:To identify the mental health condition of mothers after experiencing abortion. Method:This is a descriptive qualitative study with frequency distribution. Sampling was conducted using purposive sampling technique, and the research instrument used was a questionnaire. Results:The results showed that 12 out of 13 respondents reported experiencing mental health disturbances after abortion, with suspected depression being the most prevalent (92%). Other reported conditions included self-harm tendencies (8%), anxiety (8%), and psychosis (8%). The most common symptoms were sadness/depressed mood, followed by lack of interest or pleasure in enjoyable activities, sleep disturbances, and feelings of fatigue, digestive issues, headaches, or other prolonged physical complaints. Among the 13 respondents, the timing of abortion varied (7 respondents were 1–2 days post-abortion, and 6 respondents were 2–3 weeks post-abortion), resulting in varied psychological symptoms and recovery periods. Conclusion:The mental health condition of mothers post-abortion in the maternity ward of Pangeran Jaya Sumitra Regional Hospital, Kotabaru, is categorized as disturbed mental health, predominantly depression. This condition requires support not only from medical professionals but also the involvement of husbands, families, and the surrounding environment in efforts to prevent mental health disorders. Keywords: Mental Health, Psychological, Abortion